2017
DOI: 10.1167/17.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tilt illusion induced by continuous contextual orientation alternations

Abstract: In the classic tilt illusion, the perceived orientation of a center patch is shifted away from its oriented context. Additionally, a stronger illusion effect is yielded when the center patch is simultaneously rather than asynchronously presented with a constant context for a shorter duration. However, little is known about the temporal characteristic of the tilt illusion in a reverse situation in which a constant center patch is presented throughout while the contexts change. Therefore, we continuously alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…Another supportive evidence for this lateral inhibition mechanism was provided by our finding that the simultaneous contrast effect of gender was mediated by the temporal synchrony between the central and surrounding stimuli, as the introduction of a 500-ms temporal separation between them completely erased the simultaneous contrast effect. This echoes with previous studies on low-level features, which demonstrated a disappearance of the tilt illusion with a relatively long temporal gap (Corbett et al, 2009;Durant & Clifford, 2006;Yuan et al, 2017). It is probably because the surround suppression of neural activities lasts ~200 ms after the context disappears (Ishikawa et al, 2010;Shimegi et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another supportive evidence for this lateral inhibition mechanism was provided by our finding that the simultaneous contrast effect of gender was mediated by the temporal synchrony between the central and surrounding stimuli, as the introduction of a 500-ms temporal separation between them completely erased the simultaneous contrast effect. This echoes with previous studies on low-level features, which demonstrated a disappearance of the tilt illusion with a relatively long temporal gap (Corbett et al, 2009;Durant & Clifford, 2006;Yuan et al, 2017). It is probably because the surround suppression of neural activities lasts ~200 ms after the context disappears (Ishikawa et al, 2010;Shimegi et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of the simultaneous contrast effect is largely due to feature‐selective inhibition of neurons responding to the central stimuli (McDonald et al, 2009). Take the tilt illusion as an example, the lateral inhibition mechanism repels the perceived orientation of a vertical centre grating away from the tilted surrounding orientation (Gilbert & Wiesel, 1990; Yuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Take the well-known tilt illusion as an example; a vertical grating can be perceived away from the orientation of the surrounding context (Clifford, 2014). In addition to orientation (Clifford, 2014; Yuan et al, 2017), other basic visual properties, such as luminance (Harris et al, 2011) and size (Chen et al, 2018), have also been revealed to be perceptually susceptible to the contextual information. In general, the repulsive modulation of these visual features is explained by lateral inhibition whereby stimulated neurons are suppressed by the excitation of nearby neurons (Blakemore et al, 1970).…”
mentioning
confidence: 99%
“…The target appears repelled away from the inducer in orientation between 0° and 50° but appears rotated toward the inducer when it is between 75° and 80°. Many variations have been extended around the classical tilt illusion (Clifford & Harris, 2005; Motoyoshi & Hayakawa, 2010; Tomassini & Solomon, 2014; Yuan et al, 2017), in which a remarkable finding is that the repulsion effect can survive after the removal of the oriented surround grating from awareness (Clifford & Harris, 2005; Motoyoshi & Hayakawa, 2010) but the attraction effect requires awareness (Tomassini & Solomon, 2014). This is however different from the present study in which the attractive modulation effect appeared when the inducers were rendered invisible.…”
Section: Discussionmentioning
confidence: 99%